Goethe's Social Philosophy: As Revealed in Campagne in Frankreich and Belagerung von Mainz - Steer Jr., Alfred G. (Online access: OAPEN DOAB Directory of Open Access Books., 1955)
In this study originally published in 1955, Steer explores the importance of Goethe's family concept in two autobiographical works, "Campagne in Frankreich" and "Belagerung von Mainz". Through a close textual analysis, Steer argues that at the center of both pieces is Goethe's conception of the family as "Urform" of society.